2017
DOI: 10.21466/ac.tuibwca.2017
|View full text |Cite
|
Sign up to set email alerts
|

The ultrasound‐guided iPACK block with continuous adductor canal block for total knee arthroplasty

Abstract: Summary We report a case of pre‐operative ultrasound‐guided local anaesthetic infiltration of the interspace between the popliteal artery and the capsule of the posterior knee (iPACK), in a 75‐year‐old male undergoing total knee arthroplasty. This was supplemented with postoperative adductor canal block using a continuous catheter technique. We assessed postoperative analgesia at rest and during active flexion of the knee, opioid consumption, motor and functional recovery, and patient satisfaction, for three p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Our results suggest that an iPACK block combined with ACB can provide sufficient analgesia after orthopaedic surgery with much lower opioid consumption levels than a sham block. Other trials also have shown similar conclusions that an iPACK block with ACB can achieve better motor-sparing pain management in the immediate postoperative period compared to standard pain management protocols [9,24,25].…”
Section: Discussionmentioning
confidence: 66%
“…Our results suggest that an iPACK block combined with ACB can provide sufficient analgesia after orthopaedic surgery with much lower opioid consumption levels than a sham block. Other trials also have shown similar conclusions that an iPACK block with ACB can achieve better motor-sparing pain management in the immediate postoperative period compared to standard pain management protocols [9,24,25].…”
Section: Discussionmentioning
confidence: 66%